The word criminology (Criminology, criminal justice, law & society, 2015)
This essay looks into the past of criminology as a way to think about its future. I take a philological approach to the word criminology, looking at the etymology and history of that word, to argue for a new definition of the field: Criminology is the systematic study of crime, criminals,criminal law, criminal justice, and criminalization. I expand and explain this definition with respect to some common and (I argue) misguided dictates of criminology as it is traditionally understood. Specifically, I argue that criminology is usually but not necessarily academic and scientific, which means that criminology can be public and/or humanistic. I arrive at these thoughts by presenting some early English instances of the word criminologywhich predate the attempt to theorize a field of criminology in Italy and France in the 1880s, and I offer some new readings of those Italian and French texts. These philological analyses then come into conversation with some twentieth-century attempts to define the field and some twenty-first-century innovations in an effort to generate a definition of criminology that is responsive to the diversity of criminology in both its original formation and its ongoing transformations. Thus, the virtue of this new understanding ofcriminology is its inclusiveness: It normalizes unorthodox criminological research, which opens up new possibilities for jobs and funding in the name of criminology, which holds the promise of new perspectives on crime, new theories ofcriminology, and new policies for prevention and treatment